Salicylic acid: biosynthesis, perception, and contributions to plant immunity - Zhang, Yuelin; Li, Xin (Current opinion in plant biology, 2019)
•Salicylic acid (SA) is a plant defense hormone with critical roles in PTI, ETI and SAR.•Induction of SA synthesis is orchestrated via complex transcriptional regulation of ICS1.•SA is perceived by two types of receptors, NPR1 and NPR3/NPR4.•SA-binding activates NPR1 to promote expression of downstream defence genes.•SA-binding inhibits NPR3/NPR4, leading to de-repression of SA-responsive genes. Salicylic acid (SA) has emerged as a key plant defense hormone with critical roles in different aspects of plant immunity. Analysis of Arabidopsis mutants revealed complex regulation of pathogen-induced SA biosynthesis. Studies on SA-insensitive mutants led to the identification of the SA receptors and how SA regulates defense gene expression. Consistent with its critical roles in plant immunity, SA is required for the assembly of a normal root microbiome and various pathogen effectors have evolved to target components of SA biosynthesis or signaling. This review discusses recent advances in SA biology, focusing in particular on the regulation of SA biosynthesis and SA perception.